A mechanoresponsive nano-sized carrier achieves intracellular release of drug on external ultrasound stimulus. Issue 26 (6th June 2022) - Catania, Rosa; Onion, David; Russo, Emanuele; Zelzer, Mischa; Mantovani, Giuseppe; Huett, Alan; Stolnik, Snow
Abstract : The study illustrates feasibility of the proposed concept where intracellular drug release from mechanoresponsive liposomes can be triggered on demand by external ultrasound stimulus. Abstract : Control over intracellular release of therapeutic compounds incorporated into nano-carriers will open new possibilities for targeted treatments of various diseases including cancer, and viral and bacterial infections. Here we report our study on mechanoresponsive nano-sized liposomes which, following internalization by cells, achieve intracellular delivery of encapsulated cargo on application of external ultrasound stimulus. This is demonstrated in a bespoke cell reporter system designed to assess free drug in cytoplasm. Biophysical analyses show that drug release is attributable to the action of a mechanoresponsive spiropyran-based compound embedded in the liposomal lipid membrane. Exposure to external ultrasound stimulus results in opening of the molecular structure of the embedded spiropyran, a consequent increase in liposomal lipid membrane fluidity, and size-dependent release of encapsulated model drugs, all pointing to lipid bilayer perturbation. The study hence illustrates feasibility of the proposed concept where intracellular drug release from mechanoresponsive liposomes can be triggered on demand by external ultrasound stimulus.